Eksplorasi Interaksi Simbolik Pengemis Online di Ekosistem TikTok - Elfryda Amelia Dhamayanti; Puti Alifa Layynasha Alamsyah; Sarah Derma Ekaputri; Salsabilla Widyarto (Calathu: Jurnal Ilmu Komunikasi, 2024)
Live-streaming activities on TikTok have developed into the most popular form of content creation today because it is equipped with virtual prizes so that various types of live streaming content have emerged, one of which leads to "online begging" activities. This research used qualitative research methods through symbolic interaction studies by analyzing the relationship between actors (streamers) and audiences. The results of this study show that virtual gifts on TikTok which were originally used as a means of expression & appreciation are then used as a tool to ask for sympathy and empathy. This research also shows that the motivation of gift givers also varies from sympathy to mere entertainment. There are legal and economic aspects and determining factors that support that the phenomenon of begging in live streaming can lead to economic progress, but it does not rule out the possibility of violating the law and being prosecuted according to applicable laws and regulations. This research can be a consideration in forming regulations and intervention strategies for the government and related agencies regarding this phenomenon.